The role of working memory in sentence processing in normal reading population. A review of related literature. - Anastasia, Grammenou (Archives of Business Research, 2019)
This essay aims to describe the factors that influence sentence processing with emphasis given on garden path sentences. The latter grammatical phenomenon has been proved more problematic in people with low working memory span. Predictions of the working memory model of Baddeley and Hich and the theory of language comprehension of Just and Carpenter were used to explain sentence processing within text context.